Life of Haydn - Nohl, Ludwig, 1831-1885; Upton, George P. (George Putnam), 1834-1919 (Salt Lake City, UT : Project Gutenberg, 2022)
"Life of Haydn" by Ludwig Nohl is a biography written in the late 19th century. This work details the life of Joseph Haydn, a significant figure in classical music known as the father of the symphony and string quartet. Nohl emphasizes not just Haydn's musical accomplishments but also his personal struggles, relationships, and the whimsical aspects that made him a beloved character in the music world. The opening of the biography introduces Haydn's youth and early studies, highlighting his humble beginnings and innate musical talent. It traces his journey from a poor family in Rohrau to his education at St. Stephen's Cathedral in Vienna, where he faced both challenges and triumphs. Early anecdotes illustrate his mischievous nature and resilience in the face of hardship. Nohl presents Haydn as a lovable figure with a passion for music, setting the stage for a narrative that intertwines his creative genius with personal anecdotes that reveal his charm and human qualities. (This is an automatically generated summary.)
US
Release date is 2022-04-14
D A Alexander, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by Cornell University Digital Collections)
Keywords: Haydn, Joseph, 1732-1809